""La Vida de los Emigrantes": Digital testimonios of unaccompanied Central American high school youth. Issue 4 (18th October 2018) - McGinnis, Theresa Ann
Abstract : Purpose: In September 2014, 1, 200 unaccompanied immigrant youth, from a region of Central America known for high rates of violence and homicide, enrolled in a suburban school district of New York State. This paper aims to highlight the stories of the newly arrived Central American high school youth, as told through Bilingual (Spanish/English) digital testimonios completed in the English Language Arts classroom. The author examines how the telling of their stories of surviving migration offers a way for the youth to respond to political and emotional struggles. The author also explores how the youth become active participants in the telling of political narratives/testimonios. Design/methodology/approach: Part of a larger ethnographic case study, the author adopts the ethnographic approaches of the new literacy studies. Testimonios as a research epistemology privilege the youth's narratives as sources of knowledge, and allow the youth to reclaim their authority in telling their own stories. Findings: The integration of critical digital texts into the English Language Arts classroom created a participatory classroom culture where the Central American youth's digital testimonios can be seen as a shared history of struggles that make visible the physical toil of their journeys, the truth of their border crossings and their enactments of political identities. As a collective, the youth's stories become part of national and global political dialogues. Originality/value: At a time when immigrant youth struggle for rights, to further their education and to negotiate the daily experiences of living in a new country, this research offers a unique perspective on the politics of inclusion and exclusion for unaccompanied youth.